1993
DOI: 10.1002/j.2161-0045.1993.tb00426.x
|View full text |Cite
|
Sign up to set email alerts
|

The Inseparability of “Career” and “Personal” Counseling

Abstract: In this article it is argued that “career” and “personal” counseling should not be viewed as different types of counseling because: (a) the holistic philosophy of counseling emphasizes helping “whole” persons whose lives contain many important and meaningful roles; (b) recent research on the implications of gender and race for career development further demonstrates the inseparability of our career and “personal” lives; and (c) there are numerous commonalities in the “career” and “personal” counseling process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
1
3

Year Published

1994
1994
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 9 publications
2
63
1
3
Order By: Relevance
“…Rollin (1990) also noted that teacher-counsellors are often expected to fit counselling in with their teaching role. This finding may also be related to student attitudes toward career work (Betz & Coming, 1993;Heppner et al, 1996).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Rollin (1990) also noted that teacher-counsellors are often expected to fit counselling in with their teaching role. This finding may also be related to student attitudes toward career work (Betz & Coming, 1993;Heppner et al, 1996).…”
Section: Discussionmentioning
confidence: 90%
“…A number of studies have found that counsellors in training separate personal and career counselling and find career counselling boring (Betz & Coming, 1993), express less interest in career counselling and seek jobs which are not career-related (Pinkney & Jacobs, 1985). More recently, Heppner, O'Brien, Hinkelman and Flores (1996) found that "trainees reported significantly less ability and interest in career-vocational counselling than in social-emotional counselling" (p. 234).…”
Section: Training Of Career Personnelmentioning
confidence: 99%
“…Career intervention conceptualized in this way blurs the distinction between career counseling and psychotherapy, a distinction a growing number of authors have come to question (Betz & Corning, 1993;Blocher, 2000;Lucas, 1993;Manuele, 1992;Peavy, 1997). According to Blustein and Spengler (1995), intervention should not be based on different counseling modalities (career counseling vs. personal counseling), but rather it should be determined by each client's specific characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Counseling for work and relationship has implications for a range of intervention practices, including the specific practice of career counseling and the more general practice of counseling and psychotherapy, especially as counseling and psychotherapy is practiced by those who consider helping clients move forward in their lives as essential for successful outcomes (Summers, 2001;Wachtel, 2008) or who advocate for integrating personal and career counseling (Betz & Corning, 1993;Blustein, 2006Blustein, , 2008Blustein & Spengler, 1995;Hackett, 1993;Juntunen, 2006). It also has implications for education.…”
Section: Implications For Interventionmentioning
confidence: 99%